O diário da prática pedagógica e a construção da reflexividade na formação inicial de professores de Ciências Biológicas da UFSM - Paniz, Catiane Mazocco (2007)
This dissertation is part of the line of "Education, Knowledge and Professional Development" of the Program of Post-Graduation in Education (PPGE) of Federal University of Santa Maria (UFSM). In this work brings to the discussion a resource that can be used in the Initial Education of Biological Sciences Teachers, the Diary of the Pedagogic Practice (DPP). DPP is an instrument in which teachers register their planning following by the comments on the implementation about what is being developed in classroom, allowing a more organized organization and reflection in practical situation. It also allows the teachers to investigate, analyze and revise relative subjects to their work that frequently remain unseen to their own perception, due to the fact they are involved in the daily actions of work. The work was developed with 13 academics of the Biological Sciences Course, intending to understand how the process of reflection of their own practice occurs for these academics starting from the use of DPP. For the analysis of the diaries, I make use of the Speech Analysis, as well as a semi-structured interview. In elapsing of the work I could conclude that the diary can be an instrument to help the academics in the apprenticeship process, seeking to contribute for their personal and professional growth. Starting from the reading of the diaries it was possible to notice an evolution in the trainees' work.